Trichosanthes kirilowii Maxim. Polysaccharide attenuates diabetes through the synergistic impact of lipid metabolism and modulating gut microbiota - Qiaoying Song; Kunpeng Zhang; Shuyan Li; Shaoting Weng (Current Research in Food Science)
Polysaccharide, a chain of sugars bound by glycosidic bonds, have a wide range of physiological activities, including hypoglycemic activity. In present study, we established T2DM mice models to explore the effects and mechanism of Trichosanthes kirilowii Maxim polysaccharide (TMSP1) on high-fat diet/streptozotocin (HF-STZ) induced diabetes mice. The results showed that high-fat diet significantly increased the oral glucose tolerance test (OGTT), viscera index, oxidative stress, impaired glucose tolerance, decreased body weight, immune response and short-chain fatty acid (SCFAs) content, and disrupted the balance of intestinal flora structure. However, after 6 weeks of TMSP1 intervention decreased lipid accumulation, ameliorated gut microbiota dysbiosis by increasing SCFAs-producing bacteria and mitigated intestinal inflammation and oxidative stress. Moreover, TMSP1 significantly restored the integrity of the intestinal epithelial barrier and mucus barrier. The results of fecal microbiota transplantation confirmed that TMSP1 exerted hypoglycemic effect through regulating intestinal flora to a certain extent. Collectively, the findings revealed TMSP1 intervention inhibits hyperglycemia by improving gut microbiota disorder, lipid metabolism, and inflammation. Hence, TMSP1 may be an effective measure to ameliorate HF-STZ induced diabetes.